Reconstruction of Wooden Sleepers by Fitting in Plastic Screw Dowels - Varga, Eugen (Promet - Traffic&Transportation)
Over three million wooden sleepers are built into the Croatianrailway tracks. The durability of these sleepers depends verymuch on the fastening between the sleepers and the rails providedby the sleeper screws. The author suggests various systemsfor the fastening of the sleepers and the rails, especial v in caseof the old ones, and particularly using the plastic replacingdowels.